A Neonate with FNAIT Supported by Placental Chronic Histiocytic Intervillositis and Confounded by Maternal Preeclampsia: A Case Report - White, Hannah; Sybenga, Amelia (American Journal of Perinatology Reports, 2025)
Fetal and neonatal alloimmune thrombocytopenia (FNAIT) occurs in the setting of maternal anti-human platelet antigen (anti-HPA) antibodies against paternally derived fetal platelet antigens. Recent studies have also demonstrated an association between chronic placental inflammation and FNAIT, specifically low-grade chronic histiocytic intervillositis (CHI). We present a neonate with profound thrombocytopenia after delivery with co-occurring CHI, whose platelet counts recovered rapidly with platelet transfusions, born to a primigravida mother with late-onset preeclampsia.A male neonate was born at 40 weeks to a mother who had no known history of pregnancies, miscarriages, or transfusions. The mother developed severe preeclampsia during the induction of labor. Shortly after delivery, a physical exam of the infant showed inappropriate bruising on the heels of both feet, scattered petechiae on the hard palate, a hematoma on the left thigh after a vitamin K shot, and a bruise on the upper left abdomen. His platelet count was found to be 7,000. Platelet count rose to 94K by day 3 of life following transfusions. Placental pathology confirmed CHI. Maternal testing revealed anti-HPA-1 antibodies supporting FNAIT.This case highlights a potential relationship between maternal alloimmune response and preeclampsia. It also highlights the importance of considering FNAIT as a diagnosis in a neonate presenting with thrombocytopenia regardless of maternal preeclampsia, and the importance of submitting the placenta for a pathology exam.
Keywords: FNAIT; CHI; anti-HPA antibody